2021
DOI: 10.3390/plants10061154
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Genetic Variations of the Starch Synthase Gene Family in Rice

Abstract: Starch is a major ingredient in rice, and the amylose content of starch significantly impacts rice quality. OsSS (starch synthase) is a gene family related to the synthesis of amylose and amylopectin, and 10 members have been reported. In the present study, a synteny analysis of a novel family member belonging to the OsSSIV subfamily that contained a starch synthase catalytic domain showed that three segmental duplications and multiple duplications were identified in rice and other species. Expression data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Similar to C_3, M_3 exhibited nonsynonymous SNPs. These findings in our study were consistent with the previous findings from a GBSSII haplotype analysis that found that Hap_4 and Hap_5 were the predominant haplotypes of GBSSII haplotyping and the respective rice accessions were mostly from two major rice groups (indica in Hap_4 and japonica in Hap_5) compared to other groups, aus and admixture [20]. Simultaneously, that research group identified a key GBSSII SNP (T/G), which produces significant variations in amylose content.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similar to C_3, M_3 exhibited nonsynonymous SNPs. These findings in our study were consistent with the previous findings from a GBSSII haplotype analysis that found that Hap_4 and Hap_5 were the predominant haplotypes of GBSSII haplotyping and the respective rice accessions were mostly from two major rice groups (indica in Hap_4 and japonica in Hap_5) compared to other groups, aus and admixture [20]. Simultaneously, that research group identified a key GBSSII SNP (T/G), which produces significant variations in amylose content.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic variations (alleles) in crop species, such as SNPs, InDels, and intron length polymorphisms (ILPs), are essential to revealing molecular mechanisms, as they function in controlling traits [47][48][49][50]. Genetic variations of the starch synthase gene family has recently been updated in rice giving new insights into their correlation with improved amylose content and eating quality [20]. Using these identified variations, genetic markers have been developed for various analyses, including genetic diversity assessment, trait association mapping, and fine mapping of QTLs that regulate important agronomic traits [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starch synthase (SS) includes granule-bound starch synthase (GBSS) and soluble starch synthase (SSS). GBSS mainly catalyzes the synthesis of amylose, and SSS mainly catalyzes the synthesis of amylopectin [ 52 ]. α-Amylase (AMY) and β-amylase (BAM) are key enzymes in starch degradation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%